3D in situ observations of the compressibility and pore transport in Sheet Moulding Compounds during the early stages of compression moulding. (January 2017) - Ferré Sentis, D.; Orgéas, L.; Dumont, P.J.J.; Rolland du Roscoat, S.; Sager, M.; Latil, P.
Abstract: The properties of Sheet Moulding Compounds (SMCs) are altered by their porosity induced during the manufacturing or moulding of these prepregs. To characterise the pore scale mechanisms occurring during SMC flow, 3D synchrotron X-ray images were acquired during the compression of two uncured SMCs. For the high fibre content SMC ( 50 wt % ), with a high porosity, pores mainly decreased in size and disappeared during SMC consolidation. These mechanisms were related to the elasticity of the fibrous networks and to the permeability of the porous phase, estimated using pore scale CFD simulation. For the standard fibre content SMC ( 29 wt % ), with a lower porosity, the compressibility was limited and closed pores were transported towards the external surface of samples with non-affine motion, i.e., faster than the SMC flow and with tortuous trajectories. Besides, pores coalesced and decreased in size during compression. The size decrease was mainly related to the dissolution of pore gases.